Religious Commitment Inventory-10: On Comparison Result between Minangkabau Nomad Traders and Java Transmigrants - Herwanis, Delfia; Irham, Irham; Handrianto, Ciptro (Universitas Negeri Padang, 2021)
Religious Commitment Inventory–10 (RCI-10) in this study was used to compare the religious commitment between Minangkabau nomad traders and Java transmigrants. This research used a quantitative approach with independent sample test analysis methods. The samples of this study involved 15 respondents of Minangkabau nomad traders and 15 respondents of Java transmigrants residing in Aceh Tengah and were taken using random sampling technique. The measurements used in this study were adaptations of the RCI-10. Results of this study indicated that there is no significant difference between RCI-10 results between Minangkabau nomad traders and Java transmigrants. The conclusion is that both Minangkabau nomad traders and Java transmigrants are enjoy their lives and work in the activities of their religious affiliation.